UK parents' help‐seeking for child sleep: A qualitative investigation into parental preferences and reservations about resources. (9th August 2022) - Cook, Georgia; Appleton, Jane V.; Wiggs, Luci
Abstract: Child sleep is a common parental concern and there is an array of resources available to parents. However, an exploration of UK parents' help‐seeking behaviours around child sleep is lacking. This study sought to identify the resources parents use to seek information and help for child sleep, as well as to explore what factors parents prefer about certain sources and their reservations about using other resources. Parents of 6‐36 month old children residing in the United Kingdom (UK) completed an online questionnaire between October 2015 and October 2016 about their use, opinions and experiences regarding resources for child sleep. Quantitative data were descriptively analysed and thematic analysis was conducted on parents' open‐ended text responses. Participants were 266 UK parents (97% mothers). Parents' ages ranged from 21 to 45 years ( M = 33.49 years, SD = 4.71) and all resided in the United Kingdom (UK). General Internet searches were the most commonly reported source used by 47% of parents with a range of other informal resources also frequently consulted. Health Visitors (HVs) were the most accessed healthcare professional reportedly consulted by 38% of parents. Seven themes represented parental preferences for their resource use. Most strongly endorsed included a desire for information from other parents, particularly those with practical experience and accessing information that aligned with their parenting values. Parents preferred sources that provided support and reassurance, as well as those that afforded parents the ability to select relevant elements from a range of information. Seven themes represented parents' reservations about resources. Most strongly endorsed were concerns about reliability, being judged and challenges associated with filtering vast amounts of information. Parents reported having reservations towards sources if they had a previous negative experience with the source. Possible implications of the findings and specific suggestions about how existing and future resources could be adapted to better meet parents' needs are highlighted.